Agrobacterium tumefaciens-mediated transformation of an Oncidium orchid - Liau, C.-H.; You, S.-J.; Prasad, V.; Hsiao, H.-H.; Lu, J.-C.; Yang, N.-S.; Chan, M.-T. (Plant cell reports, 2003)
The present protocol was aimed at establishing a routine transformation procedure via Agrobacterium tumefaciens for an important Oncidium orchid cultivar. An expression vector containing hptII and gusA genes driven by the cauliflower mosaic virus (CaMV) 35S promoter was successfully introduced into the Oncidium orchid genome by A. tumefaciens. Protocorm-like bodies (PLBs) derived from protocorms, were the target explants for transformation. The transformation was performed through two stages of cocultivation, the first stage occurring on antibiotic-free medium for 3 days, and the subsequent stage on medium containing 100 mg/l timentin for 1 month. Among 1,000 inoculated PLBs, 108 putatively transformed PLBs were proliferated on 5 mg/l hygromycin selection medium. A total of 28 independent transgenic orchid plants were obtained, from which six transgenic lines that were positive for beta-glucuronidase were randomly selected and confirmed by Southern, northern and western blot analyses. These results indicated that the foreign DNA was successfully integrated into the orchid genome and expressed transcriptionally and translationally in these orchid plants. The present transformation method reported is suitable for improving the Oncidium orchid through genetic engineering.